Herpes Zoster Keratouveitis : Are We Late in Dealing with It? Poster Presentation - Case Report - General practitioner - Nurul Akla,; Ferdian Ramadhan,; Nazhira Janani, (Ophthalmologica Indonesiana, 2024)
Introduction : Herpes zoster ophthalmicus (HZO) is the viral involvement of the ophthalmic division of the trigeminal nerve. The ocular disease affects approximately 50% of HZO cases and is an ophthalmologic emergency due to the risk of vision loss if not quickly treated. This case reports the ocular complication resulting from delayed management of herpes zoster.Case Illustration : A 25-year-old woman presented with the decreased vision for one week. Physical examination revealed erythema, crusts, and multiple vesicles in the upper quadrant of the left face, with a positive Hutchinson sign. Ophthalmic examination showed a visual acuity of 0.6 on the left, with ciliary injection, a multiple dots pattern, and stromal edema in the left eye. Fine and fibrillar keratic precipitates were also present. The patient had previously received oral acyclovir 5x400 mg/day for five days after the onset of symptoms. The patient was given oral acyclovir 5x800 mg/day, amitriptyline 25 mg PO/day, homatropine ED 1 gtt/day, ofloxacin ED 4 gtt/day, Prednisolone acetate ED 4 gtt/day for the left eye.Discussion : Early management of HZO within 72 hours of rash onset is optimal. The Hutchinson sign, characterized by herpetic lesions around the nose tip, indicates nasociliary branch involvement and increases the risk of ocular involvement. Delayed or inadequate treatment can lead to various ocular complications. The prognosis is unpredictable and dependent on long-term sequelae.Conclusion : HZO keratouveitis, can result in stromal scarring or endothelial dysfunction, potentially requiring surgery if therapy is inadequate. Early recognition of ocular involvement is crucial to prevent complications and increase practitioner awareness.